Evolução do pensamento, raciocínio e desempenho em alunos do ensino superior - Emília da Conceição Figueiredo Martins; Joaquim Armando Gomes Ferreira (Revista Portuguesa de Educação, 2011)
In recent years there has been a growing interest in the academic community about the influence of higher education on cognitive development of college students. In addition to the research interest presented to professionals who are interested in studying human development across the life span, in Europe the new challenges of the Bologna Agreement brings to the forefront questions related to the impact of higher education on college students' psychosocial and cognitive development. The purpose of the present research was to longitudinally study the changes in cognitive development, reasoning and achievement, over a period of three years, in a sample of college students, attending a middle size Polytechnic School in Portugal. Results suggest positive changes in reasoning. In terms of cognitive development, results suggest a decrease in values of Relativism and Commitment in Relativism, despite the decrease values in Dualism from first year to the third year, meaning that college students over that period become less dualistic. Suggestions for research and practice are derived from the results of the present study, namely in terms of teaching and learning processes of college students.